Pengukuran Kualitas Produk dan Kualitas Pelayanan Barista terhadap Kepuasan Tamu pada Brewlah Coffee and Roastery - Wige Fransiskus Soren; Widyastuti Cahyaningrum; Syarif Hidayatullah; Yosanda Zata Aman (Jurnal Perhotelan, Destinasi Wisata, Perjalanan Wisata (Jurnal Tesla), 2023)
Brewlah Coffee and Roastery is a coffee shop business in Malang City which has been established for three years. Judging from the competition in the world of coffee shops in Malang City, it takes a good place, quality, and service to be able to compete in other culinary fields of MSMEs. This research was conducted with the aim of knowing and analyzing the quality of Barista products and services on guest satisfaction at Brewlah Coffee and Roastery. This study used 114 respondents who were guests of Brewlah Coffee and Roastery. The data collection technique was carried out by distributing questionnaires to the guests of Brewlah Coffee and Roastery randomly. The data processing method uses a simple linear reference analysis method through the SPSS program. From testing the hypothesis, it was obtained that there was a positive and significant effect partially or simultaneously between product quality and service quality on Brewlah Coffee And Roastery Guest Satisfaction. It can be interpreted that the better the product quality and service quality will further increase guest satisfaction, then other results obtained product quality has a dominant effect on guest satisfaction.